4(3x-2)=52

Simple and best practice solution for 4(3x-2)=52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x-2)=52 equation:


Simplifying
4(3x + -2) = 52

Reorder the terms:
4(-2 + 3x) = 52
(-2 * 4 + 3x * 4) = 52
(-8 + 12x) = 52

Solving
-8 + 12x = 52

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 12x = 52 + 8

Combine like terms: -8 + 8 = 0
0 + 12x = 52 + 8
12x = 52 + 8

Combine like terms: 52 + 8 = 60
12x = 60

Divide each side by '12'.
x = 5

Simplifying
x = 5

You can always share this solution

See similar equations:

| 5x^2-24x+18=0 | | 3x^2-6x+45=0 | | x^2-13=-30 | | 32+5(8.6)=n | | 5r+r+4r= | | 24=5x+6-2x | | 11r-6r+5r=168 | | 32+5(8.6)= | | 3(-14+2)=4(5-13) | | 3y+10=9 | | 3m-4=2m-13 | | 41+8z=-z^2 | | 8x+12=100 | | b-3+3b=36 | | 3y+7=9 | | 4(y+2)=5(y-5) | | 6x-10=-18x-4 | | 3x^2-15x+45=0 | | 2(-2+x)-1(x-4)=0 | | (x-6)(5x+3)=0 | | 27=y | | (x+3)(6x+7)=0 | | 2y-8=-y+4 | | 6x^2-8x+3=0 | | 0=-5h-2h | | 4h*6h= | | -2+2y=-4 | | 3-4r=10r+10 | | (3m-4n-7)-(8m+n-6)= | | 32+5n=75 | | 2y=4x-3 | | 2+11x=12x-6 | | (3m-4n-7)(8m+n-6)= | | y^2-16x-6y+25=0 | | 3(a-2)=9(a+2) | | 9x-15= | | 3=12-3x | | -7h-4=h+4 | | 62-c=42 | | -3b-2a-4c+5b-8a= | | 4d-8=19 | | 4(x-4)-11x= | | 6c-12=48 | | 25h=20h+15 | | 1-2x=16-5x | | 4y+6=-14 | | 9(6x+3)= | | 7x=11x+16 | | 3x+-7=-8 | | 9a-4a+a-10= | | 6w+5=w-35 | | 3(2t^2-5)=t | | -5x+-5=9x | | a^2x^2-8abx+16b^2=0 | | 97-4x=41x+17 | | 9=a(14) | | 11-10x=40-17x | | 10x+35=28x+35 | | -74-9x=7x+22 | | 8p-24+10p=138 | | 19r=304 | | 2x+10=-20-8x | | 9a=14 | | 3x-4-x=2x-4 | | r-17=20 |

Equations solver categories